De novo normotensive scleroderma renal crisis six years after living-donor renal transplantation in a patient with overlapping systemic sclerosis/systemic lupus erythematosus syndrome: a case report - Hajime Sanada; Satoshi Hara; Makoto Horita; Hiroyuki Kawahara; Misaki Yoshida; Yoshinori Takahashi; Shunsuke Tsuge; Takeshi Zoshima; Ryo Nishioka; Kiyoaki Ito; Ichiro Mizushima; Takashi Matsushita; et al. (BMC Nephrology, 2023)
Abstract Background Scleroderma renal crisis (SRC) is a critical kidney involvement of systemic sclerosis (SSc), often resulting in end-stage renal disease. Although the recurrence of SRC in the allograft has been reported, the development of de novo SRC after kidney transplantation has not been reported. Furthermore, normotensive SRC, which rarely occurs, makes prompt diagnosis more challenging. This fact should be recognized widely among nephrologists. Case presentation We report a 37-year-old Japanese man with overlapping SSc/systemic lupus erythematous syndrome who developed normotensive SRC in the transplanted kidney shortly after glucocorticoid escalation. Six years prior to admission, he underwent an ABO-compatible living donor kidney transplantation because of lupus nephritis. He was admitted to our hospital for gradually worsening kidney dysfunction. A kidney biopsy showed idiopathic granulomatous interstitial nephritis and high-dose prednisolone was prescribed. Although renal function improved tentatively, it deteriorated again a week later. A secondary kidney biopsy revealed acute thrombotic microangiopathy, leading to the diagnosis of normotensive SRC because all other causes were excluded, and blood pressure was within normal range. Adding an angiotensin-converting enzyme inhibitor and tapering glucocorticoid slowed the speed of deterioration of his kidney function, but he finally required hemodialysis induction. Conclusions SRC can newly develop even in the transplanted kidney, especially when high-dose glucocorticoid is administered. Normotensive SRC makes the diagnosis challenging, so nephrologists should carefully monitor patients with SSc and transplanted kidneys to treat SRC promptly.